The effect of washing cycles on the sewing properties of shirting cotton fabrics - İsler, Meral (2023)
In this study, 100% cotton poplin shirting fabric was procured and the sewing quality in different washing cycles was evaluated. For the seam strength and tensile strength tests, 5, 10 and 15 washing cycles were performed on the samples prepared both in the weft and warp directions, in accordance with the standard, using a laboratory type washing machine. At the same time, the seam efficiency values from the obtained data were calculated using the formula. The results showed that the highest tensile strength and seam strength values in both fabric directions were in the unwashed samples. It was observed that these values tended to decrease with the increase of washing cycles.